News as religion: Practices of mediation in a Catholic community in South India - Alex, Deepika Rose; Subin, Paul (SAGE, 2022)
This article examines the relationship between religion and news media through a case study of Deepika, a Malayalam-language daily published in the South Indian state of Kerala. We “thickly describe” the practices of mediation and meaning-making processes of this newspaper’s editors and readers, most of whom are “Syrian Catholics.” Our analysis shows that news functions as, or very similar to, religion for Deepika’s partakers. We thus argue that the newspaper and religion are inseparable for a devout Syrian Catholic, and they concurrently mediate the communal and spiritual longings of the believers.
Keywords: 51 Antropología; ODS 13 - Acción por el clima; mediation; Indian language press; Malayalam media; Christianity; Malayalam news; Kerala